Examination of Nursing Students' Opinions, Experiences and Attitudes Toward Medical Errors: A Cross-sectional Study - Gülcan Taşkıran Eskici; Nihal Ünaldı Baydın; Ülkü Baykal (Association of Nurse Managers, 2023)
Aim: The aim of this study was to reveal nursing students' opinions, experiences, and attitudes toward medical errors. Method: This descriptive and cross-sectional study was conducted among 465 third and fourth-year nursing students in Turkey. Data were collected between March-June 2017 using a demographic information form and the Medical Error Attitude Scale. Data analysis was performed using descriptive statistics of mean, standard deviation, number, and percentage and the Mann-Whitney U test. Results: The majority of students stated that they did not make any medical errors in clinical practice (76.8%) and if they made any medical error, they said they would report it to the charge nurse (72.7%). Only 5.8% of the students stated that they reported the medical error they made. While the students' total Scale of Attitudes toward Medical Errors mean score was 3.78 (SD=0.47), the subscale mean scores were determined to be 2.79 (SD=0.71) in the medical error perception, 3.94 (SD=0.60) in the approach to medical errors, and 3.90 (SD=0.59) in the causes of medical errors subscale. There were statistically significant differences between gender, age group, and class year of students and the Scale of Attitudes toward Medical Errors total and subscale mean scores (p<0.05; p<0.01). Conclusion: Nursing students' attitudes toward the approach to medical errors, causes of medical errors, and general medical errors were positive. In contrast, their attitude toward the medical error perception was negative. This result indicates that students' awareness of medical errors and the importance of error reporting is high. Moreover, while the majority of the students stated that they did not make medical errors in their clinical practice, they stated that the majority of medical errors were caused by doctors and nurses.